Le biografie di Stefan Zweig tra Geschichte e Psychologie: Triumph und Tragik des Erasmus von Rotterdam, Marie Antoinette, Maria Stuart - Sogos, Giorgia (Premio Ricerca «Città di Firenze», 2013)
This thesis work intends to provide a contribution in the field of research on Stefan Zweig through the in-depth study of his most famous and emblematic biographies that made the writer's fortune worldwide in the 1930s. During the research, it emerged that Zweig's biographies represent a field that has remained largely unexplored. In addition to interviews with specialists, this aspect is confirmed by the limited number of studies relating to this topic, appeared mostly in the form of not always exhaustive journal articles. Particularly, the biographies dedicated to the two queens Marie Antoinette and Maria Stuart are little taken into account, as well as the biographical study focused on the French poet Marceline Desbordes-Valmore. From the in-depth analysis of scientific sources it becomes also clear how the terminology with which these works are indicated is problematic, in that we sometimes speak of "biography" and sometimes of "novel"; sometimes these two terms appear interchangeable within a same work. With this work, an attempt was therefore made to resolve this dilemma in favour of the concept of "biography", a term which, due to its hybridity, appears not only more adequate but above all conforming to the writer's statements.